E-Procurement Practices and Sustainable Supply Chain Performance in Ghana's Local Governments: A Governance and Digital Transformation Perspective - Donkoh, Benjamin (Journal of Multidisciplinary Research Advancements, 2026)
Procurement Unit, University of Education, WinnebaThis study examines how e-procurement practices influence sustainable supply chain performance within Ghana’s Metropolitan, Municipal, and District Assemblies (MMDAs). It highlights the role of digital transformation and governance in enhancing public procurement efficiency, accountability, and transparency. A quantitative research design was employed using structured questionnaires administered to 140 MMDAs across Ghana, with 128 valid responses. Data were analyzed using descriptive and inferential statistics, including regression analysis, to determine the relationship between e-procurement practices and supply chain performance. E-procurement practices significantly improve supply chain performance, explaining 52.3% of the observed variance. The results show that e-sourcing, e-tendering, e-design, and e-evaluation contribute positively to operational and sustainability outcomes. However, inadequate ICT infrastructure, limited staff capacity, and weak legal frameworks hinder full implementation. Strengthening digital procurement capacity and institutional governance can promote transparency, reduce costs, and enhance sustainable service delivery. Policymakers should prioritise ICT investment, staff training, and regulatory reforms to maximise the benefits of e-procurement systems. This study provides empirical evidence from a developing-country context on how e-procurement practices foster sustainable and transparent public supply chains. It extends Institutional Theory and the Technology Acceptance Model (TAM) by linking technological readiness with sustainable governance outcomes.